2022
DOI: 10.3390/conservation2010007
|View full text |Cite
|
Sign up to set email alerts
|

The Decline of Common Birds Exemplified by the Western Jackdaw Warns on Strong Environmental Degradation

Abstract: Bird populations associated with agricultural ecosystems have declined markedly in Europe during the last quarter of the 20th century due to land-use intensification. This has meant that some very common species, in some cases even species considered as pests, are now threatened or subject to management programs to ensure their conservation. Considered pests of crops and predators of small game species, corvids are among the most persecuted common farmland birds. The consideration that these birds are pests la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Where animals will face many new but related informational challenges, the ability to draw on already acquired information will be a potent tool. In the case of jackdaws, a species prominent in anthropogenically altered habitats [ 48 ], regular foraging from anthropogenic refuse will be facilitated by the ability to generalize similar safe stimuli. In this study, we only varied the colour of the stimulus, with all other characteristics identical, which may not be entirely realistic, or at least does not fully explore the scope of potential stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where animals will face many new but related informational challenges, the ability to draw on already acquired information will be a potent tool. In the case of jackdaws, a species prominent in anthropogenically altered habitats [ 48 ], regular foraging from anthropogenic refuse will be facilitated by the ability to generalize similar safe stimuli. In this study, we only varied the colour of the stimulus, with all other characteristics identical, which may not be entirely realistic, or at least does not fully explore the scope of potential stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Jackdaws are highly social, colony-breeding corvids [ 68 , 69 ] with a generalist, omnivorous diet, which often includes anthropogenic foods [ 48 ]. They display high levels of neophobia towards novel foods and objects [ 33 , 36 ], form large flocks and forage socially [ 34 , 35 ], providing ample opportunities to learn from conspecifics [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Humans are altering ecosystems in many different ways that, overall, pose a much more serious threat to biodiversity than cats, such as habitat destruction for building human settlements and infrastructures, intensive agriculture, pollution, climate change, hunting, fishing, and wildlife trade (Blanco et al, 2022; Camacho et al, 2022; Ceballos et al, 2020; Coimbra et al, 2020; IPBES, 2022; Lewison et al, 2004; Newbold et al, 2020).…”
Section: The Impacts Of Cats On Biodiversity Cannot Be Generalizedmentioning
confidence: 99%
“…[ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]) benefit from urbanization all over the world. However, common species are often-neglected study objects despite their important ecological roles [ 16 , 17 ]. This is still true even after a heavy decrease in some common urban species, such as the House Sparrow ( Passer domesticus) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, low levels of predation [ 25 ], good availability of (artificial) food resources [ 26 , 27 , 28 , 29 ] as well as an availability artificial nest sites [ 13 , 30 , 31 , 32 , 33 ] may benefit corvids. However, some studies have indicated that hunting activities [ 17 , 34 ] and persecution [ 12 , 14 , 35 ] may have negative influences on corvids. The ability to use novel anthropogenic resources such as food, safe nest and roost sites [ 36 ], as well as a high tolerance towards of conspecifics may allow some species, such as corvids, to thrive in urban environments [ 37 ].…”
Section: Introductionmentioning
confidence: 99%